DECREASING CAMPUS SMOKING WITH PUNISHMENTS AND SOCIAL PRESSURES. (5th March 2018) - Clemons, Kaytlynn; Johnson, David B.; Kiger, Amy; Putnam, Janice
Abstract : This paper reports the effectiveness of a Midwest state university's "100% tobacco‐free" policy. The policy used social pressures and punishments to incentivize tobacco users to no longer consume tobacco on campus. The policy had three distinct periods (Pre‐Promotion, Post‐Promotion, and Post‐Policy). Social pressures and punishments were introduced during the Post‐Promotion and Post‐Policy periods, respectively. Changes in cigarette consumption were inferred by counting the number of cigarette butts found at various locations on campus. A statistically significant decrease in the number of cigarette butts was observed during the Post‐Promotion period. After the initial drop, tobacco use remained constant for the remainder of the period. An additional decrease was observed once punishments were introduced in the third period. However, the number of cigarette butts observed on campus remained significantly above zero. Further research is needed to understand how smokers substitute across time, location, and tobacco products after the implementation of similar policies. ( JEL I11, C99, I12)